2018
DOI: 10.1016/j.colsurfb.2018.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of DSPC/PEG40St mixtures at higher emulsifier contents

Abstract: Distearoyl-sn-glycero-3-phosphocholine (DSPC) and polyoxyethylene( 40)stearate (PEG 40 St) were investigated with Langmuir monolayer isotherms and Brewster angle microscopy (BAM) imaging at DSPC/PEG 40 St molar ratios ranging from 9:1 to 5:5. Two plateaus were found in the Langmuir isotherms which were relatively shorter for the 9:1 mixture and extended significantly by increasing the PEG 40 St content, indicating that the PEG 40 St squeezed out whereas more emulsifier retained in the monolayer at higher PEG 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
(130 reference statements)
2
8
0
Order By: Relevance
“…It was shown that microbubble stability can be improved by controlling the conformational changes in the PEG chain of the emulsifier by cooling down the microbubbles to desired temperature upon their production. As we have shown before, the another way to control conformational changes in the PEG chain of the emulsifier is to increase the PEG40St content in the formulation (40,41). Overall, the results suggest that the effect of the conformational changes induced by temperature in the PEG chain of the emulsifier should be taken into account for the design of more stable microbubbles.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It was shown that microbubble stability can be improved by controlling the conformational changes in the PEG chain of the emulsifier by cooling down the microbubbles to desired temperature upon their production. As we have shown before, the another way to control conformational changes in the PEG chain of the emulsifier is to increase the PEG40St content in the formulation (40,41). Overall, the results suggest that the effect of the conformational changes induced by temperature in the PEG chain of the emulsifier should be taken into account for the design of more stable microbubbles.…”
Section: Discussionsupporting
confidence: 61%
“…In those studies, formation of larger dark domains surrounded by emulsifier-rich continuous phase (rich-in fluorophore and therefore brighter) during slow cooling process indicates entrapment of more emulsifier molecules between condensed phase DSPC molecules (deficient in fluorophore and therefore darker) as results of PEG chains enabling to have enough time to extend into the aqueous phase and mix with condensed DSPC molecules, as discussed above. We also showed that conformational changes in the PEG chain of the emulsifier can be controlled by increasing the PEG40St content in the formulation, leading to production of more stable microbubbles (40,41). Figure 8.…”
Section: High Temperaturementioning
confidence: 86%
“…For all experiments the unit in mg/ml was utilized and the conversion mistake only came when converting to mol% to define the ratio between the coating formulation components. The correct molecular weight of PEG-40 stearate is 2046.54 g/mol (Kilic & Bolukcu, 2018;Shen et al, 2008) The authors would like to apologize for any inconvenience caused.…”
Section: Funding Informationmentioning
confidence: 99%
“…For all experiments the unit in mg/ml was utilized and the conversion mistake only came when converting to mol% to define the ratio between the coating formulation components. The correct molecular weight of PEG‐40 stearate is 2046.54 g/mol (Kilic & Bolukcu, 2018; Shen et al, 2008), not 328.53 g/mol. On page 221, it should read “The coating was composed of DSPC (84.8 mol%; Sigma‐Aldrich), PEG‐40 stearate (8.2 mol%; Sigma‐Aldrich), DSPE‐PEG(2000) (5.9 mol%; Avanti Polar Lipids) and DSPE‐PEG(2000)‐biotin (1.1 mol%; Avanti Polar Lipids).” This correction does not change the conclusions published in this study.…”
mentioning
confidence: 99%
“…For all experiments, the unit in mg/mL was utilized, and the conversion mistake occurred only when converting to mol% to define the ratio between the coating formulation components. The correct molecular weight of PEG-40 stearate is 2046.54 g/mol (Shen et al 2008;Kilic and Bolukcu 2018), not 328.53 g/mol. On page 1610, the sentence should read "The coating was composed of DSPC (84.8 mol%; P6517, Sigma-Aldrich, Zwijndrecht, The Netherlands); PEG-40 stearate (8.2 mol%; P3440, Sigma-Aldrich); DSPE-PEG(2000) (5.9 mol%; 880125P, Avanti Polar Lipids, Alabaster, AL, USA); and DSPE-PEG(2000)-biotin (1.1 mol%; 880129C, Avanti Polar Lipids)."…”
mentioning
confidence: 99%